Computational comparison of regional stress and deformation characteristics in tricuspid and bicuspid aortic valve leaflets. (24th June 2016) - Cao, K.; Sucosky, P.
Summary: The bicuspid aortic valve (BAV) is the most common congenital valvular defect and a major risk factor for secondary calcific aortic valve disease. While hemodynamics is presumed to be a potential contributor to this complication, the validation of this theory has been hampered by the limited knowledge of the mechanical stress abnormalities experienced by BAV leaflets and their dependence on the heterogeneous BAV fusion patterns. The objective of this study was to compare computationally the regional and temporal fluid wall shear stress (WSS) and structural deformation characteristics in tricuspid aortic valve (TAV), type‐0, and type‐I BAV leaflets. Arbitrary Lagrangian–Eulerian fluid‐structure interaction models were designed to simulate the flow and leaflet dynamics in idealized TAV, type‐0, and type‐I BAV geometries subjected to physiologic transvalvular pressure. The regional leaflet mechanics was quantified in terms of temporal shear magnitude (TSM), oscillatory shear index (OSI), temporal shear gradient (TSG), and stretch. The simulations identified regions of WSS overloads and increased WSS bidirectionality (174% increase in temporal shear magnitude, 0.10 increase in OSI on type‐0 leaflets) in BAV leaflets relative to TAV leaflets. BAV leaflets also experienced larger radial deformations than TAV leaflets (4% increase in type‐0 BAV leaflets). Type‐I BAV leaflets exhibited contrasted WSS environments marked by WSS overloads on the non‐coronary leaflet and sub‐physiologic WSS levels on the fused leaflet. This study provides important insights into the mechanical characteristics of BAV leaflets, which may further our understanding of the role played by hemodynamic forces in BAV disease. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Fluid‐structure interaction models were designed to compare the regional stress and deformation characteristics of tricuspid aortic valve and bicuspid aortic valve (BAV) leaflets. BAV hemodynamic abnormalities were found to be morphotype‐dependent and leaflet‐dependent. BAV leaflets experience larger radial deformations, higher wall shear stress (WSS) levels and more pronounced WSS bidirectionality than TAV leaflets. Type‐I BAV leaflets exhibit contrasted hemodynamics marked by WSS overloads on the non‐coronary leaflet and sub‐physiologic WSS levels on the fused leaflet.